- #1

- 13

- 0

Well,I've tried attempting this problem but I am not sure if I approached it the right way. Here is a link for the diagram and the question.

[PLAIN]http://img.photobucket.com/albums/v367/crazy_cat_lady/physics/diagram1.bmp[/URL] [Broken]

If anyone could check it over and point out any mistakes and tell me if I make any sense what so ever,then you would make my day.

My solution:

Fe=Fg therefore

qE=mg ------> E=mg/q

x-component: Ex¹= Ecosø

= Fe/q cosø

= mg/q cosø

y-component: Ey¹= Esinø

= Fe/q sinø

= mg/q sinø

E¹= square root of (mg/cosø)² + (mg/sinø)²

Another solution that I thought up of:

Isn't tension just the sum of all forces acting on a object...therefore:

Ft= Fe+Fg

Fe= Fg-Ft

= mgsinø- Ft

[PLAIN]http://img.photobucket.com/albums/v367/crazy_cat_lady/physics/diagram1.bmp[/URL] [Broken]

If anyone could check it over and point out any mistakes and tell me if I make any sense what so ever,then you would make my day.

My solution:

Fe=Fg therefore

qE=mg ------> E=mg/q

x-component: Ex¹= Ecosø

= Fe/q cosø

= mg/q cosø

y-component: Ey¹= Esinø

= Fe/q sinø

= mg/q sinø

E¹= square root of (mg/cosø)² + (mg/sinø)²

Another solution that I thought up of:

Isn't tension just the sum of all forces acting on a object...therefore:

Ft= Fe+Fg

Fe= Fg-Ft

= mgsinø- Ft

Last edited by a moderator: